2023
DOI: 10.3390/plants12112147
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial and Wound Healing Properties of Natural Products: A Review on Plant Species with Therapeutic Potential against Staphylococcus aureus Wound Infections

Ana Elisa Belotto Morguette,
Guilherme Bartolomeu-Gonçalves,
Gabriella Maria Andriani
et al.

Abstract: Wounds of an acute or chronic etiology affect millions of people worldwide, with increasing prevalence every year. Microbial infections are one of the main causes that impair the wound healing process, and Staphylococcus aureus, a commensal member of the skin microbiota, is one of the main causative agents of wound infections. Crucially, a high proportion of these infections are caused by methicillin-resistant Staphylococcus aureus, which, in addition to β-lactams, has acquired resistance to almost all the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 100 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…38 For the management of infected wounds, strategies aimed at anti-infection and promoting healing should be employed, thus striking a balance between inflammation and tissue remodeling. 39 Numerous studies have demonstrated that the flavonoids and Carbopol 940 hydrogel possess wound-healing properties due to their well-acclaimed anti-inflammatory, antioxidant, re-epithelialization, and angiogenesis effects. 14,40–43 In our previous report, QU in combination with LU enhanced the antibacterial and antibiofilm efficacy synergistically, decreasing the membrane permeability and down-regulating the expression of multiple biofilm-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…38 For the management of infected wounds, strategies aimed at anti-infection and promoting healing should be employed, thus striking a balance between inflammation and tissue remodeling. 39 Numerous studies have demonstrated that the flavonoids and Carbopol 940 hydrogel possess wound-healing properties due to their well-acclaimed anti-inflammatory, antioxidant, re-epithelialization, and angiogenesis effects. 14,40–43 In our previous report, QU in combination with LU enhanced the antibacterial and antibiofilm efficacy synergistically, decreasing the membrane permeability and down-regulating the expression of multiple biofilm-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the active compounds that are gaining importance in promoting wound healing are a wide variety of natural products, like plant extracts. These are characterized by containing numerous bioactive compounds with antimicrobial, immunoregulatory and antioxidant properties [11][12][13]. Thus, interesting therapeutic properties have been extensively reported for OELE, partly related to its antioxidant and anti-inflammatory capacities [14,15].…”
Section: Introductionmentioning
confidence: 99%